Airway Hyperresponsiveness in Asthma: Mechanisms, Clinical Significance, and Treatment - Brannan, John D.; Lougheed, M. Diane (Frontiers in Physiology, 2012)
Airway hyperresponsiveness (AHR) and airway inflammation are key pathophysiological features of asthma. Bronchial provocation tests (BPTs) are objective tests for AHR that are clinically useful to aid in the diagnosis of asthma. BPTs can be either ‘direct’ or ‘indirect’, referring to the mechanism by which a stimulus mediates bronchoconstriction. Direct BPTs refer to the administration of pharmacological agonist (e.g., methacholine or histamine) that act on specific receptors on the airway smooth muscle. Airway inflammation and/or airway remodeling may be key determinants of the response to direct stimuli. Indirect BPTs are those in which the stimulus causes the release of mediators of bronchoconstriction from inflammatory cells (e.g., exercise, allergen, mannitol). Airway sensitivity to indirect stimuli is dependent upon the presence of inflammation (e.g., mast cells, eosinophils), which responds to treatment with inhaled corticosteroids (ICS). Thus, there is a stronger relationship between indices of steroid-sensitive inflammation (e.g., sputum eosinophils, fraction of exhaled nitric oxide) and airway sensitivity to indirect compared to direct stimuli. Regular treatment with ICS does not result in the complete inhibition of responsiveness to direct stimuli. AHR to indirect stimuli identifies individuals that are highly likely to have a clinical improvement with ICS therapy in association with an inhibition of airway sensitivity following weeks to months of treatment with ICS. To comprehend the clinical utility of direct or indirect stimuli in either diagnosis of asthma or monitoring of therapeutic intervention requires an understanding of the underlying pathophysiology of AHR and mechanisms of action of both stimuli.